Penentuan Efisiensi Immobilisasi Kromium (VI) Pada Geopolimer Abu Sekam Padi Dengan Uji TCLP (Toxicity Characteristic Leaching Procedure) - Kun Sri Budiasih (EKSAKTA: Journal of Sciences and Data Analysis, 2011)
This research aimed  to determine  the efficiency of immobilization of Cr(VI) on  the rice husk  ash  based  geopolymer with  a TCLP  (Toxicity Characteristic  Leaching Procedure)  study. The TCLP was    refer  to  the  standard method  from  Japan  Environmental  Agency. There were three  variables  used  i.e.,    concentration  of Cr(VI)  impregnated,  particles  size,  and  the  kind  of leaching  water. Determination  of  immobilization  efficiency  was  done  by  calculate  the concentration  of  Cr(VI)  in  the  leachate  water  after    the  leaching  processes.    Quantitative measurement of the chromium was done by Uv-Vis spectrometer with biphenyl carbazid  reagent. Immobilization of Cr(VI) on the rice husk ash based  geopolymer was establish until 25 ppm Cr impregnated. The efficiency of the immobilization can reach 90% - almost 100% depend on the variable of leaching processes.   Keywords: eficiency, immobilization, geopolimer, rice husk ash, TCLP study